Effect of annealing temperatures on microstructural evolution and corrosion behavior of Ti-Mo titanium alloy in hydrochloric acid. (1st April 2022) - Wei, Ya; Pan, Zhimin; Fu, Yu; Yu, Wei; He, Shilei; Yuan, Qingying; Luo, Hong; Li, Xiaogang
Abstract: In this work, the corrosion and passive behavior of Ti-3Mo titanium alloy with various annealing temperatures from 750 °C to 1050 °C in 20 wt% hydrochloric acid solution is investigated via electrochemical measurements, static immersion test, X-ray photoelectron spectroscopy and scanning electron microscopy. The results show that the corrosion rate increases with an increase in annealing temperature, which is attributed to the accelerated dissolution of the passive film after the annealed temperature above 850 °C and the formation of microgalvanic cells by α- and β-phase. Moreover, the passive film displays the n-type semiconductor properties independent of annealing temperature. Highlights: Corrosion resistance of Ti-3Mo titanium alloy was strongly affected by the annealing temperature. The stability of the passive film in 20 wt% HCl solution decreased with an increase in annealing temperature. Chemical dissolution and microgalvanic corrosion were the main causes in corrosion of Ti-3Mo titanium alloy.